Efektivitas Metode Suku Kata dalam Meningkatkan Kemampuan Membaca Permulaan bagi Siswa ADHD - Annisa May Syarah Nasution; Ardisal Ardisal (Jurnal Penelitian Pendidikan Khusus, 2022)
This research discusses the improvement of early reading skill in ADHD student using the Syllable Method at SD Muhammadiyah Padangsidimpuan. The research of this study is the third grade ADHD student in SD Muhammadiyah Padangsidimpuan. This study uses Single Subject Research and the type of experimental research with A-B-A design, baseline (A1), intervention (B), baseline (A2). Data collection in this study was done through observation, interviews, and tests. The data collection tool uses frequency. The reseacrh data is analyzed using graphs. Based on the result of study, it was stated that the initial reading abilty of ADHD student increased after intervention using the Syllable Method was given. So it can be concluded that the Syllbale Methos can improve the early reading ability of ADHD student.